Evolutionary Roots of Arginase Expression and Regulation - Dzik, Jolanta Maria (Frontiers in Immunology, 2014)
Two main types of macrophage functions are known: classical (M1), producing nitric oxide, NO, and M2, in which arginase activity is primarily expressed. Ornithine, the product of arginase, is a substrate for synthesis of polyamines and collagen, important for growth and ontogeny of animals. M2 macrophages, expressing high level of mitochondrial arginase, have been implicated in promoting cell division and deposition of collagen during ontogeny and wound repair. Arginase expression is the default mode of tissue macrophages, but can also be amplified by signals, such as IL-4/13 or transforming growth factor-β (TGF-β) that accelerates wound healing and tissue repair. In worms, the induction of collagen gene is coupled with induction of immune response genes, both depending on the same TGF-β-like pathway. This suggests that the main function of M2 “heal” type macrophages is originally connected with the TGF-β superfamily of proteins, which are involved in regulation of tissue and organ differentiation in embryogenesis. Excretory–secretory products of metazoan parasites are able to induce M2-type of macrophage responses promoting wound healing without participation of Th2 cytokines IL-4/IL-13. The expression of arginase in lower animals can be induced by the presence of parasite antigens and TGF-β signals leading to collagen synthesis. This also means that the main proteins, which, in primitive metazoans, are involved in regulation of tissue and organ differentiation in embryogenesis are produced by innate immunity. The signaling function of NO is known already from the sponge stage of animal evolution. The cytotoxic role of NO molecule appeared later, as documented in immunity of marine mollusks and some insects. This implies that the M2-wound healing promoting function predates the defensive role of NO, a characteristic of M1 macrophages. Understanding when and how the M1 and M2 activities came to be in animals is useful for understanding how macrophage immunity, and immune responses operate.